The Principle of Materiality and Its Practical Implementation in the Integrated Reporting of Corporate Enterprises - Bezverkhiy, K. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The materiality principle of materiality is central to the integrated reporting system of corporate enterprises, because, international practices confirm that to be informative, reports have to contain essential information defined by stakeholders and by company itself for taking effective management decisions. Yet, the materiality principle is not subject of much concern by the Ukrainian corporate sector when preparing, compiling, submitting and publishing integrated report. This raises the importance of studies on this principle implementation in integrated reports of Ukrainian corporate enterprises. The objective of the study is to analyze implementation of the materiality principle in integrated reports of Ukrainian corporate enterprises by addressing the problems: (i) to give the characteristics of the materiality principle for financial reporting purposes; (ii) to show objects and materiality thresholds for individual forms of financial reporting; (iii) to describe the procedure of determining the materiality for integrated reporting purposes; (iv) to analyze the materiality aspects of integrated reports made by Ukrainian corporate enterprises; (v) to offer recommendations on implementing the materiality principle in integrated reporting of Ukrainian companies in keeping with international principles of integrated reporting. Practical use of the materiality principle in integrated reporting of Ukrainian corporate enterprises is illustrated by the sample of three companies: “NAKNAFTOGAS of Ukraine”, “DTEK”, and “BDO” Ltd. Recommendations for Ukrainian corporate enterprises on practical use of the materiality principle in integrated reporting are (i) to include the materiality principle in the main part of integrated reporting, with its description in the element “main principles of preparation and presentation”, which has been missing by far in integrated reporting of Ukrainian corporate enterprises; (ii) to use this principle for describing integrated reporting elements specified in the International Guidelines of Integrated Reporting: review of organization and external environment, management, business model, risk management, resource allocation strategy, operative results, future perspectives etc.